Analysis of scientific production on the inclusion in Brazilian higher education - Pletsch, Marcia Denise; Leite, Lucia Pereira [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2017)
Since the 90's, the rights of people with disabilities have been part of national and international debates. In this context, the principles of inclusive education have been incorporated into Brazilian educational guidelines, but their extension from early childhood education to higher education has been most notably recognized from 2008 onwards, through the propagation of the National Policy of Special Education in the inclusive education perspective. Focusing on higher education, this paper starts from the analysis of the thematic as treated in the scientific production available in the Scientific Electronic Library Online database (SciELO-BRAZIL). The results showed that, despite the advances in the production of knowledge on the subject, it still falls short of the demand, which grows at an accelerated rate, largely due to the development of public policies that foster the participation of students with disabilities. This aspect puts universities facing a number of issues beyond infrastructure, such as the ones of pedagogical, social and attitudinal order.
Keywords: Public policies of inclusive education; Higher education; Deficiency